Are you IDDSI ready?. (2nd February 2019) - Boaden, Elizabeth; Lightbody, Elizabeth; Watkins, Caroline
Abstract : The International Dysphagia Diet Standardisation Initiative (IDDSI) global framework was launched in November 2015. It was subsequently adopted by the Royal College of Speech and Language Therapists and the British Dietetic Association, following expert review and professional membership consultation. In the UK, NHS England established an IDDSI External Reference Group, comprising stakeholders including professional, catering, industry and manufacturing representatives. The IDDSI External Reference Group have endorsed an Aware, Prepare, Adopt model of implementation, and all manufacturers and all healthcare settings are expected to be fully IDDSI compliant by April 2019. This requires whole system change, with a comprehensive training programme. Those providing and delivering food and drink to individuals with swallowing difficulties need to familiarise themselves with food and drink consistencies, and their testing methods. Resources are available to assist local healthcare institutions with implementation of the framework (at:www.rcslt.org /www.bda.org /www.iddsi.org ).